Evaluation of Phobia, Knowledge, Attitude and Practice about SARS-CoV-2 Infection, a Study on Healthcare Workers and Their 1st Degree Relatives - Hosseinzadeh, R.; Hosseini, S. M.; Karbasi, A.; Maghari, A.; Fathi-Ashtiani, A.; Heiat, M.; Bahardoust, M.; Ranjbar, R.; Badri, T. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Phobia as a psychological disorder seems to be aggravated during health crises like the current COVID-19 outbreak. On the other hand, people’s knowledge about a situation can help decrease the resulting fear. Study design. This is a cross-sectional analytical study to evaluate the COVID-19 related phobia and to measure knowledge, attitude, and practice of our target Iranian population about COVID-19.Methods. In this study, DSM-5 specific phobia questionnaire, adapted to SARS-CoV2-19 infection, was used to evaluate the COVID-19 related phobia. Moreover, the knowledge, attitude, and practice (KAP) questionnaire, specific for SARS-CoV-2  infection, was applied.Results. Phobia score was significantly higher in 1st-degree relatives of healthcare staff (20.38±5.82) than healthcare staff (18.36±5.68) (p=0.021). Females showed a significantly more severe phobia (20.27±5.41) than males (17.72±5.35, p=0.001). COVID-19 phobia was significantly more severe in those with past psychiatric conditions than in those without psychiatric history (p